Intergeracionalidade na Profissão Docente: Tensões Estruturais e Horizontes Formativos à Luz de Evidência Europeia (Revista Lusófona de Educação, 2026)
Intergenerationality in the Teaching Profession: Structural Tensions and Educational Horizons in the Light of European EvidenceThis article develops a theoretical and conceptual analysis of teaching as an intergenerational profession, grounded in an interpretative documentary review methodology centred on the Education and Training Monitor 2025 (European Commission, 2025). This European source is complemented by relevant academic literature and recent Portuguese documentation, namely the Annual Statistical Reports – Indicators of Immigrant Integration (AIMA, 2025), the State of Education reports (CNE, 2024), and policy guidelines issued by the Directorate-General for Education (DGE, 2022). The analysis of these documents highlights the persistence of structural tensions within the teaching profession, including the ageing of the teaching workforce, the fragility of generational renewal, the declining attractiveness of the profession, and limitations in effective access to continuing professional development. Evidence reported at both European and national levels also points to significant challenges in preparing teachers to respond to educational contexts marked by cultural and social diversity and to address sensitive issues pedagogically. These dynamics are understood as structural in nature, relating to fragmented models of teacher education and to the absence of consistent mechanisms for intergenerational learning and reflective supervision. On the basis of this review, the article supports the conceptualisation of teaching as an intergenerational epistemological community, in which professional knowledge is constructed collectively, contextually, and ethically. For the Portuguese context, it argues for a model of teacher education guided by principles of intergenerationality, collaboration, historical literacy, and lifelong learning, as a condition for strengthening the sustainability of the teaching profession.Keywords: Professional Development; Teacher Education; Intergenerationality; Portugal; European Reports; Sensitive Topics.